The kinematics modeling and parameter optimization of six-wheel lunar exploration robot. (7th May 2018) - Guodong, Zhai; Peiyuan, Gao; Lili, Meng
This article proposes a six-wheel lunar exploration robot which will move on the lunar surface. It is known that lunar surface is mostly rugged. When the six-wheel lunar exploration robot moves on the rugged surface, its centroid position will change, which has an impact on the vehicle obstacle performance and anti-overturning performance, and so on. Therefore, it is very important to analyze the centroid domain of the robot. In order to get the relation between centroid domain and position as well as the posture equation during the motion process, the kinematics model of the robot is built based on the coordinate transforming relations. So the calculation formula of centroid domain and body posture equation at any movement position are obtained. The mathematical model of detection robot is analyzed by entity analysis. So the centroid vector model of radial angle change curve and the changing rule of both sides of the rocker arm angle and centroid vector mode are given. MATLAB [version 6.0] is used to optimize the parameters of the robot and ADAMS is used to simulate the process when the robot moving on the rugged lunar surface. The results show that the centroid domain is a flat area. Based on the calculations and simulations, the vertical displacement and the pitch angle of the robot are decreased with different degrees after the optimization of the rocker arm suspension and the integrated moving stable performance of the lunar exploration robot is obviously enhanced.